O reformach studiów prawniczych i nauczaniu prawa w Polsce w latach 1918–2015 - Wojtczak, Krystyna (Wydawnictwo Naukowe UAM, 2015)
Starting from the Second Republic of Poland until recent times, the basic trend of all discussions regarding the framework of educating lawyers has been directed to answering the questions: (i) whether legal studies are to educate for the need of science, research and didactics or practice, or (ii) whether perhaps they should offer education, which would reconcile both of these qualities. A positive response to each of these questions corresponds to a balance among the adopted curriculum subjects: theoretical and historical as well as dogmatic. In the period under review, either of the two solutions was legally acceptable. The model in force in the Second Republic strongly promoted educating the university lawyer, that is one whose knowledge was built on reconciling the theoretical and historical subjects with law dogmatics. The period of Polish People’s Republic and later years decisively deviated from this pattern, and the proposed law teaching models were changing. The changes went from solutions which placed emphasis on preparing law students to practise the legal profession, then in the mid-sixties, brieﬂy, this trend was reversed in favour of legal studies preparing for professions, which required mastery of a speciﬁc area of scientiﬁc knowledge for scholarly work, research and didactics, ﬁnally in the following years to more strongly emphasise a return to the model of education of lawyers practitioners. It was only in the early nineteen eighties that a broader framework of law universities autonomy was created, and then preserved in the early years of the Third Polish Republic. The choice of educational model for lawyers took on a new meaning in the optics of adoption by Poland in 1999 of the principles of the Bologna Declaration. In 2007, through the implementation of educational standards, law studies were brought closer to the model of university studies. This approach was abandoned in 2011 by adopting proﬁles for legal studies education (general academic know- ledge – practical), deﬁned only in 2014, while not giving each school or college the freedom to choose the model (proﬁle) of teaching law.
On the reforms of legal studies and teaching law in Poland in the years 1918–2015
Keywords: legal determinants of educating lawyers; disputes over legal education model; evaluation of legal studies programmes before and after signing of the Bologna Declaration by Poland